The taxonomy of the topminnows (Teleostei: Cyprinodontiformes) (Procatopodidae: Procatopodinae) of southern Africa - Van Zeeventer, Ryan Matthew (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2020)
Taxonomy is a tool that plays a crucial role in the implementation of effective management assessments, the ability to identify different fish species and their life stages, and create effective conservation strategies. Recent years have seen an increase in the discovery of cryptic species which could have an effect on how we implement conservation strategies, increasing the importance of accurate taxonomic assessments. The southern African topminnows of the genera Micropanchax and Lacustricola (Family Procatopodidae) include several species of egg-laying fishes that live in the marginal areas of rivers and lakes throughout the river systems of southern Africa in separated and connected populations. It was recently discovered that these populations showed subtle differences in their morphology and colouration, which led to the belief that new and cryptic species may be present. Previous studies of the Procatopodidae relied heavily on phylogenetic analyses that drew on morphological traits without reliance on molecular methods of analysis. A few of the taxonomic issues were resolved through these limited studies but ultimately the taxonomic status of the Procatopodidae remained poorly understood. Furthermore, these studies had not been updated in recent years and hence the benefits of new technology had not been brought to bear on the issues. A multi-gene analysis using standard phylogenetic methods and five molecular markers (mitochondrial cytochrome C oxidase (COI), mitochondrial cytochrome b (cytb), mitochondrial 16S ribosomal RNA (16S rRNA), nuclear 28S ribosomal RNA (28S rRNA) and mitochondrial Tyrosine Kinase (X-src) (TyrK)) allowed phylogenetic trees to be made which demonstrated clear relationships within Micropanchax and Lacustricola of southern Africa and the out-groups used in the analysis. The inference trees showed that Micropanchax johnstoni was represented by three clades and was shown to be polyphyletic while Micropanchax hutereaui, which was represented by two clades, and Micropanchax katangae, which was represented by one clade, were monophyletic. The two species of Lacustricola, L. myaposae and L. macrurus showed very close relationships to Micropanchax and it is suggested that these two species be transferred to Micropanchax, leaving Lacustricola to only be found in central Africa.
Keywords: Cyprinodontiformes -- Africa, Southern; Killifishes -- Africa, Southern